Speed, Quality, and the Optimal Timing of Complex Decisions: Field Evidence - Uwe Sunde; Dainis Zegners; Anthony Strittmatter (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper presents an empirical investigation of the relation between decision speed and decision quality for a real-world setting of cognitively-demanding decisions in which the timing of decisions is endogenous: professional chess. Move-by-move data provide exceptionally detailed and precise information about decision times and decision quality, based on a comparison of actual decisions to a computational benchmark of best moves constructed using the artificial intelligence of a chess engine. The results reveal that faster decisions are associated with better performance. The findings are consistent with the predictions of procedural decision models like drift-diffusion-models in which decision makers sequentially acquire information about decision alternatives with uncertain valuations.
Keywords: D01; D90; C70; C80; 330; response times; speed-performance profile; drift-diffusion model; uncertain evaluations